2022
DOI: 10.3390/nano12234229
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Induced µ-Rooms for Osteocytes on Implant Surface: An In Vivo Study

Abstract: Laser processing of dental implant surfaces is becoming a more widespread replacement for classical techniques due to its undeniable advantages, including control of oxide formation and structure and surface relief at the microscale. Thus, using a laser, we created several biomimetic topographies of various shapes on the surface of titanium screw-shaped implants to research their success and survival rates. A distinctive feature of the topographies is the presence of “µ-rooms”, which are special spaces created… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Veiko et al irradiated the surface of the Ti implant with a laser and obtained three different micromorphology surfaces by adjusting the trajectory of the laser. 62 As shown in Figure 5B and C, compared to the nonsurface treatment, the surface of the implant irradiated by a laser showed obvious and regular distribution of microscopic texture. Subsequent in vivo experiments showed that the G-shape texture had the most significant effect on osseointegration.…”
Section: Laser Radiationmentioning
confidence: 91%
See 3 more Smart Citations
“…Veiko et al irradiated the surface of the Ti implant with a laser and obtained three different micromorphology surfaces by adjusting the trajectory of the laser. 62 As shown in Figure 5B and C, compared to the nonsurface treatment, the surface of the implant irradiated by a laser showed obvious and regular distribution of microscopic texture. Subsequent in vivo experiments showed that the G-shape texture had the most significant effect on osseointegration.…”
Section: Laser Radiationmentioning
confidence: 91%
“…These techniques can be broadly classified into two types. The first type is surface treatment, such as sandblasting, , acid etching, , anodizing, , and laser irradiation. , These technologies effectively modify the roughness, hardness, and oxidation of Ti. The other type is coating.…”
Section: Surface Modification Techniques For Dental Implantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Laser texturing proves to be a precise, accurate, reproducible, and environmentally friendly technique for modifying surfaces. Literature findings reveal that the laser-texturing process not only results in an enhancement of tribological behavior attributed to improved lubrication [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ], but also leads to superior microbiological properties owing to the contact guide effect [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%